Inhibition of platelet-derived growth factor (PDGF) receptor affects follicular development and ovarian proliferation, apoptosis and angiogenesis in prepubertal eCG-treated rats. (5th September 2015) - Pascuali, Natalia; Scotti, Leopoldina; Abramovich, Dalhia; Irusta, Griselda; Di Pietro, Mariana; Bas, Diana; Tesone, Marta; Parborell, Fernanda
Highlights: PDGFR inhibitor AG1295 decreased the percentage of PAFs and EAFs and increased the percentage of AtFs in eCG-treated rats. AG1295 affected ovarian weight and E2 levels in eCG-treated rats. AG1295 decreased cell proliferation and increased apoptosis in ovaries from eCG-treated rats. AG1295 decreased the endothelial cell area and the peri-endothelial cell area in ovaries from eCG-treated rats. Abstract: The platelet-derived growth factor (PDGF) system is crucial for blood vessel stability. In the present study, we evaluated whether PDGFs play a critical intraovarian survival role in gonadotropin-dependent folliculogenesis. We examined the effect of intrabursal administration of a selective platelet-derived growth factor receptor (PDGFR) inhibitor (AG1295) on follicular development, proliferation, apoptosis and blood vessel formation and stability in ovaries from rats treated with equine chorionic gonadotropin (eCG). The percentages of preantral follicles (PAFs) and early antral follicles (EAFs) were lower in AG1295-treated ovaries than in control ovaries (p < 0.01–0.05). The percentage of atretic follicles (AtrFs) increased in AG1295-treated ovaries compared to control (p < 0.05). The ovarian weight and estradiol concentrations were lower in AG1295-treated ovaries than in the control group (p < 0.01 and p < 0.05, respectively), whereas progesterone concentrations did not change. AG1295 decreased the proliferation index in EAFs (p < 0.05) and increased the percentage of nuclei positive for cleaved caspase-3 and apoptotic DNA fragmentation (p < 0.01–0.05). AG1295 increased the expression of Bax (p < 0.05) without changes in the expression of Bcl-2 protein. AG1295-treated ovaries increased the cleavage of caspase-8 (p < 0.05) and decreased AKT and BAD phosphorylation compared with control ovaries (p < 0.05). AG1295 caused a decrease not only in the endothelial cell area but also in the area of pericytes and vascular smooth muscle cells (VSMCs) in the ovary (p < 0.05). Our findings suggest that the local inhibition of PDGFs causes an increase in ovarian apoptosis through an imbalance in the ratio of antiapoptotic to proapoptotic proteins, thus leading a larger number of follicles to atresia. PDGFs could exert their mechanism of action through an autocrine/paracrine effect on granulosa and theca cells mediated by PDGFRs. In conclusion, these data clearly indicate that the PDGF system is necessary for follicular development induced by gonadotropins.